2013
DOI: 10.1007/s00381-013-2057-0
|View full text |Cite
|
Sign up to set email alerts
|

Sprengel’s deformity and spinal dysraphism: connecting the shoulder and the spine

Abstract: The combination of spinal dysraphism and Sprengel's deformity is rare, and is associated with segmentation defects of the spine and ribs. Although the etiology of both spinal dysraphism and Sprengel's deformity remains unclear, all deformities of the spine, ribs, and shoulder might result from a common genetic defect affecting somitogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The locations are not randomly distributed over the neural tube ( P = 2.0*10 −5 ) but show a preference for the occipital region, vertebrae C6 till T3 and the region between T8 and S1 with a peak at L5. (Richards et al, ; Tekkok, ; Etus et al, ; Singh and Singh, ; Srinivas et al, ; Ahmad and Mahapatra, ; Vashu and Liew, ; Bear et al, ; Carmody et al, ; Dankovcik et al, ; Singh and Singh, ; Singh et al, ; Vogel et al, ; Ahmed et al, ; Herman et al, ; Leykamm et al, ; Mahalik et al, ; Meuli et al, ; Sarici et al, ; van Aalst et al, ; Yang et al, ; De la Calle et al, ; Garg et al, ; Gressot et al, ; Hawasli et al, ; Leoni et al, ; Meadows and Hayes, ; Meunier et al, ; Perez da Rosa et al, ; Anand and Mahmoud, ; Canaz et al, ; Hanaei et al, ; Paul et al, ; Radtke et al, ; Ramdurg et al, ; Sargar et al, ; Wood et al, ; Arishima et al, ; Clark and Davidson, ; Dickman et al, ; Dorum et al, ; Santos et al, ; Sharma et al, ; Zhou and Zheng, ). [Color figure can be viewed at http://wileyonlinelibrary.com]…”
Section: Materials and Methods And Resultsmentioning
confidence: 99%
“…The locations are not randomly distributed over the neural tube ( P = 2.0*10 −5 ) but show a preference for the occipital region, vertebrae C6 till T3 and the region between T8 and S1 with a peak at L5. (Richards et al, ; Tekkok, ; Etus et al, ; Singh and Singh, ; Srinivas et al, ; Ahmad and Mahapatra, ; Vashu and Liew, ; Bear et al, ; Carmody et al, ; Dankovcik et al, ; Singh and Singh, ; Singh et al, ; Vogel et al, ; Ahmed et al, ; Herman et al, ; Leykamm et al, ; Mahalik et al, ; Meuli et al, ; Sarici et al, ; van Aalst et al, ; Yang et al, ; De la Calle et al, ; Garg et al, ; Gressot et al, ; Hawasli et al, ; Leoni et al, ; Meadows and Hayes, ; Meunier et al, ; Perez da Rosa et al, ; Anand and Mahmoud, ; Canaz et al, ; Hanaei et al, ; Paul et al, ; Radtke et al, ; Ramdurg et al, ; Sargar et al, ; Wood et al, ; Arishima et al, ; Clark and Davidson, ; Dickman et al, ; Dorum et al, ; Santos et al, ; Sharma et al, ; Zhou and Zheng, ). [Color figure can be viewed at http://wileyonlinelibrary.com]…”
Section: Materials and Methods And Resultsmentioning
confidence: 99%
“…Experience is required in both methods and our case is a lesson in humility for the very experienced team of radiologists. Nonetheless, to the best of our knowledge, in this case, we were dealing with a hitherto unknown constellation of anomalies, although deformities of vertebral bodies, including Klippel-Feil syndrome, deformities in or the absence of ribs, genitourinary anomalies, and spinal dysraphism (myelomeningocele, posterior MC, tethered cord) have already been described, always postnatally, in association with Sprengel’s deformity [21]. We have found neither a description of the associated lateral MC protruding through the neural foramen, nor of its coexistence with vestigial posterior MC and lipoma tethering of the cord to the dural sac at the cervical-thoracic junction.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we compared the clinical features in our patient with previous cases diagnosed with CM-II and Sprengel’s deformity (Table 2 ) [ 12 ]. Although the genotypes were not available for all these cases, we found multiple segmentation defects of the spine, ribs, and shoulder among these patients, which suggests that these symptoms might result from a common genetic defect affecting somitogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Their results indicated that the parts of the skeleton affected in CM-I/II, Sprengel’s deformity and the Klippel­Feil syndrome all derive from a specific population of neural crest cells, suggesting these diseases might have a similar developmental origin. However, research on the association between spinal dysraphism and Sprengel’s deformity is scarce [ 12 ].…”
Section: Introductionmentioning
confidence: 99%